Interpretation and Expression of Violin Soloist in Playing: Concerto In E Major, My Heart Will Go On, and Laila Canggung - Nasrullah, M.; Sidik, Hadaci; Wijaksana, Bambang; Enida, Delfi; Dary, Mohammad (Scoring: Journal of Film Music, 2025)
Performances of musical repertoire from various eras, such as classical, modern, Malay, and popular, are wrapped into a solo violin performance in the form of interpretation and expression of works using musical performance techniques that contain conventional rules. This performance consists of several repertoires from different eras. The first repertoire is a repertoire that originates from the baroque era or the 16th century, entitled Concerto in E Major No. 1 Spring, with a combination of Antonio Vivaldi, which was created in 1725. The second repertoire is My Heart Will Go On, which is popular. The third repertoire is Laila Awkward, which Hamid and Amardi Raga created. Presenters interpret and express their repertoire by applying techniques such as arpeggios, trills, legato, and slurs to create a perfect performance.